Topical pharmacologic interventions versus placebo for epidemic keratoconjunctivitis - Kuo, Irene C (Cochrane Database Syst Rev, 2020)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy and safety of various topical pharmacological therapies versus placebo for adults with epidemic keratoconjunctivitis (EKC).